2003
DOI: 10.1159/000069940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urticaria pigmentosa with Café-au-Lait Spots, Neurofibromas and Neurofibroma-Like Neoplasms: A Mere Coincidence?

Abstract: Background: Urticaria pigmentosa (UP) is characterized by dense aggregates of mast cells in the dermis. There is consistent evidence from the literature that mast cells may play a pathogenetic role in the development of neurofibromas and other tumors. Objective: To study the concomitant appearance of UP with neurofibromas and neurofibroma-like neoplasms. Methods: We analyzed 31,752 records of patients examined at the Department of Dermatology in the year 2000, looking for UP and associated neurofibromas and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The factors promoting the development of neurofibromas are not clear. It has been reported that in urticaria pigmentosa cases mast cells might play a causative role in the development of neurofibroma and neurofibroma-like lesions [8]. Similarly in this case, some tumorigenic factors secreted by bronchoalveolar carcinoma cells may be responsible for the development or acceleration of neurofibromas in this patient.…”
supporting
confidence: 56%
“…The factors promoting the development of neurofibromas are not clear. It has been reported that in urticaria pigmentosa cases mast cells might play a causative role in the development of neurofibroma and neurofibroma-like lesions [8]. Similarly in this case, some tumorigenic factors secreted by bronchoalveolar carcinoma cells may be responsible for the development or acceleration of neurofibromas in this patient.…”
supporting
confidence: 56%
“…The condition presented here may be a new clinical entity that should be added to the list of disorders characterized by multiple lentigines. It is noteworthy that mastocytosis has been associated with café-au-lait macules [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Darier's sign was positive with no dermographism ( fi g. 1 b). There was no other clinical anomaly on physical examination, especially no lymph node enlargement and no hepatomegaly or splenomegaly, no fl ushing and no signs suggestive of concomitant neurofi bromatosis [1] . The complete blood count and the other biological examinations were normal except that there was a slight increase in both the plasma level of histamine (61 nmol/l; normal: 5-25) and the urinary level of prostaglandin D 2 (226 ng/mmol; normal: 40-200).…”
mentioning
confidence: 94%